Mutual effects of fine particulate matter, nitrogen dioxide, and fireworks on cause-specific acute cardiovascular mortality: A case-crossover study in communities affected by aircraft noise. (15th December 2021) - Saucy, Apolline; de Hoogh, Kees; Vienneau, Danielle; Tangermann, Louise; Schäffer, Beat; Wunderli, Jean-Marc; Probst-Hensch, Nicole; Röösli, Martin
Abstract: Ambient air pollution is the leading cause of environmental mortality and morbidity worldwide. However, the individual contributions to acute mortality of traffic-related air pollutants such as nitrogen dioxide (NO2 ) and fine particulate matter (PM2.5 ) are still debated. We conducted a time-stratified case-crossover study for a population located around Zurich airport in Switzerland, including 24, 886 adult cardiovascular deaths from the Swiss National Cohort. We estimated the risk of cause-specific cardiovascular mortality associated with daily NO2 and PM2.5 concentrations at home using distributed lag models up to 7 days preceding death, adjusted for daily temperature, precipitation, acute night-time aircraft noise, firework celebrations, and holidays. Cardiovascular mortality was associated with NO2, whereas the association with PM2.5 disappeared upon adjustment for NO2 . The strongest association was observed between NO2 and ischemic stroke mortality (odds ratio = 1.55 per 10 μg/m 3, 95% confidence intervals = 1.20–2.00). Cause-specific mortality analyses showed differences in terms of delayed effect: odds ratios were highest at 1–3 days after exposure for most outcomes but at lags of 3–5 days for heart failure. Individual vulnerabilities to NO2 associated cardiovascular mortality also varied by cause of death, possibly highlighting the role of different behaviours and risk factors in the most susceptible groups. The risk of cardiovascular mortality was also increased on firework days and after public holidays, independent from NO2 and PM2.5 concentrations. This study confirms the association between ambient NO2, as a marker for primary emissions, and acute cardiovascular mortality in a specific setting around a major airport. Future research should clarify the role of additional air pollutants including ultra-fine particles on cardiovascular diseases to inform most efficient control measures. Graphical abstract: Image 1 Highlights: Cardiovascular mortality associated with NO2 levels around a major airport. Highest NO2 risk observed for ischemic stroke mortality. No association of PM2.5 with cardiovascular mortality after adjustment for NO2 . Increased cardiovascular mortality in relation to national firework days.